Relationship Mothers’ Knowledge, Family’s Income, Family Role and Basic Immunization Status - Efi Isnayni (Universitas Airlangga, 2016)
Immunization is the most effective government effort to reduce infectious diseases, so as to reduce child mortality. Immunization coverage in Indonesia has not yet reached the specified target. Many factors affect the completeness of basic infant immunization including factors from parents and family. The purpose of this study was to analyze the relationship between the mother's knowledge and the role of the family and the basic immunization status of infants. This research was an observational analytic study using a cross-sectional design. Sampling using cluster random sampling techniques. The sample in this study was 46 mothers of infants aged 9-12 months who were in the Public health center (PHC) of Pucuk’s working area, Lamongan District. Data analysis used was a Chi-square test with significance level α = 0.05. The results showed a relationship between maternal knowledge (p = 0.027), the role of the nuclear family (p = 0.007), and the role of the non-nuclear family (p = 0.020) with the basic immunization status of infants. There was no relationship between family income and infant basic immunization status (p = 0.725). The conclusion of the research is the mother's knowledge and the role of the family has an important role to increase the coverage of basic immunization for infants, so it is necessary to improve the communication of information and education for mothers about the complete basic immunization that must be obtained by the baby.